Sosialisasi Hidroponik dalam Pemanfaatan Lahan yang Minim Sebagai Potensi Peluang Bisnis di Masyarakat RT 21 Kelurahan Lamaru Kota Balikpapan - Nofan, Nofansyah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Hydroponics is a method of growing plants using a medium other than soil. instead, plants are grown in a water medium that contains a nutrient solution, rich in the minerals needed by the plant. This approach utilizes water circulation, allowing even small areas to be maximized for plant cultivation. Hydroponic methods offer several advantage, such as faster plant growth, flexible planting space, efficient water use, and reduced pesticide requirements. There are various types of hydroponic systems,including: (NFT) Nutrient Film Technique that is; a thin layer of nutrient solution flows over the plant roots, (DFT) Deep Film Technique that is; nutrient solution is maintained at a certain depth around the roots, Wick System that is; nutrients are transported to the roots through an absorbing medium, (DBS) Dutch Bucket System that is; uses buckets or pots filled with growing media (such as hydroton, broken tiles, or pumice). The hydroponic program in RT 21, Lamaru Village, Balikpapan City, has received positive feedback. This initiative not only boosts the enthusiasm of local residents and youth but also demonstrates promising business potential in horticultural cultivation in residential areas. This activity is beneficial and has the potential to become an attractive business opportunity.